A case of compound heterozygous hemoglobin Köln/hemoglobin E in an Indian family. (18th August 2019) - Mittal, Navkirti; Garg, Akanksha; Kashyap, Rajesh; Agarwal, Sarita
Abstract: Hemoglobin Köln, is the most common unstable hemoglobin variant worldwide, yet has only rarely been reported in Indians. Herein we report a case of coinheritance of Hb Köln and Hb E, which to the best of our knowledge has not been reported in the literature so far. The patient presented with mild symptoms of hemolysis with no previous history of blood transfusions.